Crop Production and Soil Properties Impacts of Integrating Annual Forages and Ruminant Livestock into Wheat-based Cropping Systems - Zachariah C. Carson; Augustine K. Obour; John D. Holman; Kraig L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2024)
Integrating annual forages and ruminant livestock to intensify dryland cropping systems can increase profitability, increase water use efficiency, and improve soil health. The objective of this study was to determine the crop yield and soil property impacts of intensifying traditional no-till winter wheat (Triticum aestivum L.)-grain sorghum (Sorghum bicolor Moench)-fallow (WW-GS-F) with annual forages as well as integrating livestock to graze forages and crop residues. This study was initiated in 2021 at the Kansas State University Agricultural Research Center-Hays in Hays, KS. Treatments were WW-GS-F (control), WW-GS-F with grain sorghum residues grazed, winter wheat/forage sorghum-forage sorghum-fallow (WW/FS-FS-F) with forage sorghum grazed, and WW/FS-FS-F with forage sorghum hayed. The treatments were replicated four times with all phases of the rotation present each year. Grain and forage yields were determined every year with sampling to characterize soil properties in fall 2023. Results showed that full-season forage sorghum harvested for hay produced 5,994 lb/a on average, while post-wheat forage sorghum harvested for hay produced 1,682 lb/a. Before grazing, full-season forage sorghum produced 9,735 lb/a with about 51% of biomass remaining as residue after livestock were removed. On average, post-wheat forage sorghum produced 2,988 lb/a before grazing. Because of smaller yields, post-wheat forage sorghum plots were grazed only in one year when 82% of biomass remained as residue on the plots after livestock were removed. In 2023, WW yields were low due to dry weather, but there was no difference among treatments and average was 15 bu/a. The WW/FS-FS-F (grazed) treatment had greater crop residue cover (77%) at winter wheat planting than all other treatments (53%) in fall 2023. No differences in bulk density or penetration resistance in the 0 to 2-inch and 2 to 6-inch soil depths were observed across treatments. Despite no differences in bulk soil organic carbon (SOC) in the 0 to 2-inch and 2 to 6-inch soil depths, dry aggregate associated SOC was greater with WW-GS-F (grazed) and WW/FS-FS-F (grazed) treatments than WW-GS-F and WW/FS-FS-F (hayed). No differences in mean weight diameter (MWD) of water stable aggregates or the wind-erodible fraction were observed across treatments. These preliminary results suggest that intensifying the WW-GS-F rotation with annual forages and integrating livestock increased available forage, soil residue cover, and dry aggregate associated organic carbon with no effect on winter wheat yields.
Keywords: annual forages; grazing; soil properties